A re-examination of musharakah bonds and Waqf development: the case of Singapore - Abdullah, Adam; Saiti, Buerhan (International Islamic University Malaysia, 2016)
This research re-examines the structured financing involving two waqf real estate development projects in Singapore and the issuance of musharakah bonds in 2001 and 2002. This study seeks to address how and why the financing was structured. Moreover, the research had no influence over the behavioural events surrounding these transactions and that the projects are both contemporary in nature. The methodology involves case study research, including documentary and content analysis of selected materials. In terms of analytical generalization and external validity, we adopt the framework of the Islamic normative theory of profit. The study finds that despite the noble intention of the Islamic Religious Council of Singapore (MUIS) to issue musharakah bonds in developing the waqf properties in assessing substance over form, they do not satisfy the conditions relating to a valid contract and lawful income. Accordingly, we recommend an alternative mechanism for the future development of waqf projects, structured on the basis of a real estate investment trust.